åˆ©ç”¨å¯¹æ¯”æ•™å¦æ³•æé«˜å¤ç”¸ABDI AGAPE ä¸ä¸“å¦æ ¡äºŒå¹´çº§å¦ç”Ÿ å¦ä¹ åŠ©è¯â€”â€”â€œçš„â€ã€â€œå¾—â€ä¸Žâ€œåœ°â€çš„èƒ½åŠ› - Hidayati, Nur Fajrina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning Chinese grammar can not be separated from learning Chinese vocabulary. In daily life, there are several commonly used words, such as noun, verb, and so on. Beside verb, noun, measure word, we have to learn particle. Particle is common used among sentences. The particles that we commonly see are